NUMERICAL CALCULATION OF MAGNETIC FIELD INDUCTION IN THE WORK AREA LINEAR PERMANENT MAGNET MOTOR WITH A MASSIVE CONDUCTOR IN BY THE INTEGRAL EQUATIONS METHOD - ZHILTSOV, А.; SOROKIN, D. (Енергетика і автоматика, 2015)
In work based on Maxwell's equations using the method of secondary sources of the mathematical model for the calculation of the magnetic field in the working area coaxial linear motor with permanent magnets considering losses due to eddy currents in massive elements of the engine has been developed.